Increasing vegetable intake to obtain the health promoting and ergogenic effects of dietary nitrate. Issue 11 (November 2018) - Avoort, Cindy; Loon, Luc; Hopman, Maria; Verdijk, Lex
Abstract Increased consumption of dietary nitrate increases plasma nitrate and nitrite concentrations, and has been shown to elicit cardio-protective effects and improve exercise performance. Nitrate consumption in the habitual diet is mainly dependent on nitrate-rich vegetables, such as green leafy and root vegetables, with total vegetable consumption accounting for approximately 50–85% of our daily nitrate intake. Whereas 'supplementation' with dietary nitrate in research studies has mainly been accomplished through the use of (concentrated) nitrate-rich beetroot juice, dietary strategies focusing on increased intake of nitrate-rich vegetables may represent a similarly effective alternative for increasing dietary nitrate intake and, as such, obtaining the associated cardiovascular health and ergogenic benefits.